Yatırım fonu ve yatırım ortaklıklarının vergilendirilmesi - Kıranoğlu, Tülün (My University, 2001)
Tek bir piyasa olma yönünde dünyada yaşanan gelişmeler, globalleşme olgusu beraberinde en önemli unsuru olan sermayenin akıcı olmasını gerektirdiğinden, sermaye piyasası kurulları giderek ulusal/ uluslar arası alanda önem kazanmıştır. Sermaye piyasası kurumları arasında yer alan yatırım fon ve ortaklıklarının asıl kurulma nedeni olan küçük tasarruf sahiplerinin yatırımlarının daha az riskli bir şekilde ve uzman bir kadro tarafından yatırıma kanalize edilmesi bu iki kuruma diğer sermaye piyasası kurumları içinde daha ayrıcalıklı bir yer tanımıştır. Yatırım fon ve ortaklıklarındaki bu ayrıcalık beraberinde bu iki kuruma vergi teşviklerinin tanınmasını getirmiştir. Bu çalışmanın asıl konusunu bahsi geçen vergi teşviklerinin gerek vergi mevzuatındaki diğer hükümler ile olan uyumu, gerekse sermaye piyasası mevzuatı ile ilişkisi oluşturmaktadır. The course of events that run towards the emergence of a sole market, in other words, the fact of globalization, entails ıts most important element, the capital to be fluıd, the capital and the ınstitutions of market are acquiring importance. The main function of the establihment of the investment funds and partnership which take place among the ınstitutions of capital market is to protect the minor investors aganist risks and to channel their savings to the investmentin the hand of a qualified team in a safer way. This function raised these two ınstitution to a previaling status among the other ones. The privelage that the ınstitution of investment funds and partnership is attained for this privailing character of the ınstitutions of investment funds and partnership, some financial facilities have been attained to them for their improvement. The main goal of this study is to eliminate the contradictions and to accord above mantioned financial facilities in the term of substantive law of tax and the law of capital market.
Keywords: Yatırım Fonları